The Charlie Brown dictionary - Schulz, Charles M. (Charles Monroe), 1922-2000.; Wright, Wendell W., (Wendell William), 1893- (New York : Random House, 1973)
Based on "The Rainbow Dictionary," this dictionary contains 2400 entries included on the basis of frequency of use by children from five to eight years old.
Based on The rainbow dictionary by Wendell W. Wright.
Library Journal.
3.4
K-3
Keywords: Picture dictionaries, English -- Juvenile literature; Picture dictionaries; English language -- Dictionaries; Picture dictionaries; Picture dictionaries, Chinese; Chinese language dictionaries